E2F7 Transcriptionally Inhibits MicroRNA-199b Expression to Promote USP47, Thereby Enhancing Colon Cancer Tumor Stem Cell Activity and Promoting the Occurrence of Colon Cancer - Guo, Xiong; Liu, Ling; Zhang, Qi; Yang, Weiming; Zhang, Yang (Frontiers in Oncology, 2021)
microRNAs (miRNAs or miRs) can modulate gene expression at the post-transcriptional level and are closely related to the growth and metastasis of colon cancer. Herein, we aimed to explore how miR-199b influences colon cancer and to characterize its underlying molecular mechanism associating with E2F transcription factor 7 (E2F7). RT-qPCR, Western blot analysis and immunohistochemistry were used to detect E2F7 expression in tissue samples collected from 30 patients diagnosed with colon cancer. Flow analysis was utilized to detect the ratio of ALDH1+ and CD133+ colon cancer stem cells. The interaction between E2F7, miR-199b, USP47, and MAPK was identified by ChIP-Seq analysis, dual luciferase reporter assay, RNA pull-down assay, co-immunoprecipitation, and GST pull-down experiments. Through gain- and loss-of-function approaches in cells, the effects of E2F7 in regulating the miR-199b/USP47/MAPK axis on colon cancer cell proliferation, migration, and invasion, as well as the tumorigenesis were assessed. E2F7 was highly expressed in colon cancer tissues, and E2F7 silencing reduced the production of ALDH1+ and CD133+ colon cancer stem cells and antagonized the effects of 5-fluorouracil (5-FU) treatment and oxidative stress, proliferation, migration, and invasion of ALDH1+ cells in vitro, and on tumorigenesis of colon cancer cells in vivo. Our findings reveal the pro-oncogenic role of E2F7 in the progression of colon cancer and show that E2F7 may be a novel therapeutic target for patients with colon cancer.